2019
DOI: 10.1016/j.celrep.2018.12.065
|View full text |Cite
|
Sign up to set email alerts
|

Double Lock of a Human Neutralizing and Protective Monoclonal Antibody Targeting the Yellow Fever Virus Envelope

Abstract: Highlights d The crystal structures of YFV-E in both pre-and post-fusion states are determined d A neutralizing monoclonal antibody engages YFV-E in both states as a double lock d This monoclonal antibody inhibits YFV infection at multiple steps of virus entry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 53 publications
2
53
0
Order By: Relevance
“…The relatively high abundance of these two germline genes (VH4-4 and VL1-51) in the naïve B cell repertoire perhaps provides a molecular explanation for how the YFV-17D vaccine is able to induce protective neutralizing Ab responses in such an extraordinarily high proportion of individuals (>95%) (42,43). Furthermore, a subset of these nAbs displayed exceptionally potent neutralizing activity, with IC 50 s that were about 10 times lower than previously described YFV mAbs (13,14). Given the recent YFV outbreaks in Brazil and the Democratic Republic of…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The relatively high abundance of these two germline genes (VH4-4 and VL1-51) in the naïve B cell repertoire perhaps provides a molecular explanation for how the YFV-17D vaccine is able to induce protective neutralizing Ab responses in such an extraordinarily high proportion of individuals (>95%) (42,43). Furthermore, a subset of these nAbs displayed exceptionally potent neutralizing activity, with IC 50 s that were about 10 times lower than previously described YFV mAbs (13,14). Given the recent YFV outbreaks in Brazil and the Democratic Republic of…”
Section: Discussionmentioning
confidence: 92%
“…Our work provides key insights into the B cell response underlying the efficacy of the YFV-17D vaccine, which may facilitate the design of vaccines for more refractory pathogens, such as malaria and HIV. mAbs described to date target overlapping epitopes within DII of the E protein (13,14).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Sequence alignment revealed that DIII is the most variable domain among the flavivirus E proteins (Fig. 3A), and thus, antibodies targeting DIII are more likely to be species specific (21 (38,(40)(41)(42)(43)(44)(45)(46) (Fig. 3).…”
mentioning
confidence: 99%
“…Thus, MAb 5A prevents both virus attachment and fusion. As the fusion loop is a highly conserved antigen, there is a high possibility that 5A neutralizes other flaviviruses [76]. In the same way, Wu et al [77] identified a panel of human MAbs that target DIII of the ZIKV envelope protein from a large Phage Display naïve antibody library.…”
Section: Application Of Phage Display In the Context Of Denv And Othementioning
confidence: 99%